Inflation-forecast targeting : applying the principle of transparency - Clinton, Kevin (IMF working paper ;, 2015)
"Many central banks in emerging and advanced economies have adopted an inflation-forecast targeting (IFT) approach to monetary policy, in order to successfully establish a stable, low-inflation environment. To support policy making, each has developed a structured system of forecasting and policy analysis appropriate to its needs. A common component is a model-based forecast with an endogenous policy interest rate path. The approach is characterized, among other things, by transparent communications - some IFT central banks go so far as to publish their policy interest rate projection. Some elements of this regime, although a work still in progress, are worthy of consideration by central banks that have not yet officially adopted full-fledged inflation targeting."--Abstract